Crete reclaimed : a feminist exploration of bronze age Crete - Evasdaughter, Susan; Castleden, Rodney; Walker-John, Billie (Loughborough : Heart of Albion Press, 1996)
Bibliotheek François Vercammen
Engels
Monografie